2006
DOI: 10.1163/156854106778877848
|View full text |Cite
|
Sign up to set email alerts
|

Seinura lii n. sp. and S. wuae n. sp. (Nematoda: Seinuridae) from pine wood in China

Abstract: Seinura lii n. sp. and S. wuae n. sp. are described and illustrated from dying Pinus massoniana infested with Bursaphelenchus xylophilus in China. Seinura lii n. sp. is characterised by relatively long female and male bodies (763-1146 and 831-1068 µm, respectively), stylet 16-20 µm long and lacking knobs, two rows of developing oocytes in the anterior gonad, welldeveloped postuterine sac (120-182 µm long), three lines or incisures in the lateral field, four pairs of subventral papillae on the male tail region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Till now, S. aurangabadensis (Suryawanshi, 1971), S. elmiraensis (van der Linde, 1938;Goodey, 1960), S. filicaudata (Christie, 1939;Goodey, 1960), S. oahueensis (Christie, 1939;Goodey, 1960), S. oostenbrinki (Husain and Khan, 1967), S. steineri (Hechler, 1965 in Hechler andTaylor, 1965), S. tenuicaudata (de Man, 1895;Goodey, 1960), and S. tritica (Bajaj and Bhatti, 1982) have been documented from China (Jiang, 2000;Xie and Zhang, 2003;Huang and Ye, 2008;Feng, 2010;Ding et al, 2013;Zhang et al, 2013). The two previously described species S. lii (Huang and Ye, 2006) and S. wuae (Huang and Ye, 2006) from China are now transferred to Aphelenchoides (Fischer, 1894) and Bursaphelenchus , respectively (Gu et al, 2017;Kanzaki et al, 2018).…”
mentioning
confidence: 99%
“…Till now, S. aurangabadensis (Suryawanshi, 1971), S. elmiraensis (van der Linde, 1938;Goodey, 1960), S. filicaudata (Christie, 1939;Goodey, 1960), S. oahueensis (Christie, 1939;Goodey, 1960), S. oostenbrinki (Husain and Khan, 1967), S. steineri (Hechler, 1965 in Hechler andTaylor, 1965), S. tenuicaudata (de Man, 1895;Goodey, 1960), and S. tritica (Bajaj and Bhatti, 1982) have been documented from China (Jiang, 2000;Xie and Zhang, 2003;Huang and Ye, 2008;Feng, 2010;Ding et al, 2013;Zhang et al, 2013). The two previously described species S. lii (Huang and Ye, 2006) and S. wuae (Huang and Ye, 2006) from China are now transferred to Aphelenchoides (Fischer, 1894) and Bursaphelenchus , respectively (Gu et al, 2017;Kanzaki et al, 2018).…”
mentioning
confidence: 99%
“…Six years later, Goodey considered that this species belongs to the genus Ektaphelenchus Fuchs, 1937, with A. stammeri being a synonym of E. stammeri (Körner, 1954) Goodey, 1960 [1,3,4]. In 2006, the species Seinura lii was described by Huang and Ye and in 2019 was transferred to the genus Aphelenchoides Fisher, 1894, and named A. lii (Huang & Ye, 2006) Kanzaki, Ekino & Masuya, 2019 [5,6]. According to these authors, the taxonomy of A. stammeri needed to be revised, and they suggested that A. lii should be transferred to a new genus or synonymised with A. stammeri.…”
Section: Introductionmentioning
confidence: 99%
“…damaged trees [7]. Afterwards, in 2006, it was detected in Pinus massoniana Lambert, 1803; infected with Bursaphelenchus xylophilus (Steiner & Bührer, 1934) Nickle, 1981, in China [5]; isolated from the dead wood of P. sylvestris Linnaeus, 1758, in Slovenia [8]; and later, reported to be associated with P. massoniana, in Turkey [9], observed in packaging wood imported from Spain, and observed in declining P. massoniana, in China [2]. Moreover, some rDNA Potensaphelenchus stammeri sequences (LSUrDNA) from nematodes associated with P. pinaster Aiton, 1789, in Portugal, have been deposited in the NCBI database (accession numbers MG647830, MT786210, and MT786211).…”
Section: Introductionmentioning
confidence: 99%
“…Andrássy (1993) contributed significantly to the taxonomy of the genus Mononchus. Species of Seinura (Fuchs, 1931) have been recorded from the pine trees infested with pine wilt nematode, Bursaphelenchus xylophilus from in USA and China (Huang and Ye, 2007). Jana et.al.…”
Section: Introductionmentioning
confidence: 99%